Act of valor - Mentink, Dana (Love inspired suspense., 2019)
"When airline employee Violet Griffin encounters several suspicious passengers, she's thrust into the crosshairs of a drug smuggling operation. NYPD officer Zach Jameson and his drug detection beagle, Eddie, can tell this is no small-time threat. Someone's gunning for Violet, and after recently losing his brother, Zach refuses to lose her, too...especially now that she's gone from friend to the woman he's falling for." -- Page [4] cover.